The Title Threshold in the Collection ’’Qal… Fadel’’ by the Algerian Poet ’’Faisal Lahmar’’ - Zemmour, Kenza; Kherfi, Mohamed Salah (Journal of Human Sciences, 2023)
We aim in this study to monitor the strategic foundations on which the phenomenon of selective and conscious assignment of the title system based in the Algerian poet "Faisal Lahmar"’s Collection "Qal...Faddel" by modeling it according to the schema of literary communication. Through which we control the interactive movement of the title within the communicative environment in which it participates in reporting through "relationship" and "function". Those, which change according to the nature of the poles, related to this textual threshold, in order to monitor its functional effectiveness in the semantic production act associated with achieving a linguistic structure through which the discourse load is concentrated or through its longitudinal fragmentation in the folds of the text. Moreover, we examine it as a textual value that aims to win the pragmatic bet to work with the writer’s authorization on aesthetic and intellectual values that aim to multiply the effect on the reader.